God, Yoga, and Karate. - Yi, Joseph; Silver, Daniel (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2015)
We investigate the location patterns of organizations that embody key religious-spiritual traditions and that have grown to prominence in the latter 20th and early 21st centuries: evangelical churches, yoga, and martial arts. The distribution of key cultural organizations depends on the degree to which they are able to frame themselves in relation to one another and to core American traditions. Organizations associated with the American religious divide are more polarized in their social appeal and spatial distributions, and those framed as broadly neutral elements of popular culture are more widely distributed. Using a national database of local amenities, we find that theologically conservative churches are popular in many neighborhoods but concentrated in less-educated and nonwhite areas. Yoga studios are less geographically dispersed and more spatially concentrated in collegeeducated and white areas. Compared to these, martial arts schools, sports clubs, and other pop-culture amenities are more widely distributed across different types of areas.